Correlative Assessment of Interdental and Interradicular Bone Loss in Horizontal and Vertical Bone Defects In Chronic Periodontitis: A Clinical and Radiographic Study: Pharmaceutical Science-Periodontics for Dental Health - Dr Shreya Shetty; Dr Othman Wali; Dr Khalied Alharthi; Dr. Abdulrahman Mengash; Dr Abdulaziz Maleh; Dr Irfan Adil; Khamrunissa Hussain Sheikh (International Journal of Life Science and Pharma Research, 2022)
It is important to treat periodontitis before involvement of furcation areas because of their complex anatomy and difficulty of access. Literature confirms that it is difficult to accurately determine the relationship of the amount of bone loss in the interdental areas associated with the interradicular areas and correlate them with the clinical periodontal status. The aim of this study was therefore to assess the existence of such an association, if any, in subjects with chronic periodontitis. The threshold of alveolar bone loss associated with progression of periodontal destruction and involvement of interradicular areas of the furcations is not clearly defined in the literature. The aim of this study was to investigate a correlation, if any between interdental and interradicular bone loss and clinical parameters in patients with chronic periodontitis. Periapical (IOPA) radiographs of mandibular molars were obtained from 193 sites in 33 males and 21 females between the age group of 25 and 55 years having chronic periodontitis. These were then scanned and digital measurement of linear distances was performed using dicom software of height and width of defect (horizontal and vertical), bone defect angle and interradicular bone loss. These measurements were correlated to pocket depth (PD) and clinical attachment loss (CAL) using One-way ANOVA followed by Tukeys HSD post hoc tests. Bone height significantly correlated with probing depth and CAL in horizontal defects (p<0.005) with hardly any furcation involvement (1.55%)whereas both bone height and width showed significant correlation with probing depth and CAL in vertical defects(P<0.001) with nearly 77% of sites showing furcation defects. A strong correlation of clinical parameters with bone defect dimensions suggests that early diagnosis and management of interdental bone loss may be critical to prevent furcation involvement.